Do Nonsuicidal Severely Depressed Individuals with Diabetes Profit from Internet-Based Guided Self-Help? Secondary Analyses of a Pragmatic Randomized Trial - Sandra Schlicker; Kiona K. Weisel; Claudia Buntrock; Matthias Berking; Stephanie Nobis; Dirk Lehr; Harald Baumeister; Frank J. Snoek; Heleen Riper; David D. Ebert (Journal of Diabetes Research)
Introduction. Diabetes mellitus type 1 and type 2 are linked to higher prevalence and occurrences of depression. Internet-based depression- and diabetes-specific cognitive behavioral therapies (CBT) can be effective in reducing depressive symptom severity and diabetes-related emotional distress. The aim of the study was to test whether disease-specific severity indicators moderate the treatment outcome in a 6-week minimally guided web-based self-help intervention on depression and diabetes (GET.ON Mood Enhancer Diabetes (GET.ON M.E.D.)) and to determine its effectiveness in a nonsuicidal severely depressed subgroup. Methods. Randomized controlled trial- (RCT-) based data (N=253) comparing GET.ON M.E.D. to an online psychoeducation control group was used to test disease-specific severity indicators as predictors/moderators of a treatment outcome. Changes in depressive symptom severity and treatment response were examined in a nonsuicidal severely depressed subgroup (CES−D>40; N=40). Results. Major depressive disorder diagnosis at the baseline (pprf6=0.01), higher levels of depression (Beck Depression Inventory II; pprpo=0.00; pprf6=0.00), and lower HbA1c (pprpo=0.04) predicted changes in depressive symptoms. No severity indicator moderated the treatment outcome. Severely depressed participants in the intervention group showed a significantly greater reduction in depressive symptom severity (dprpo=2.17, 95% Confidence Interval (CI): 1.39-2.96) than the control condition (dprpo=0.92; 95% CI: 0.001-1.83), with a between-group effect size of dprpo=1.05 (95% CI: 0.11-1.98). Treatment response was seen in significantly more participants in the intervention (4/20; 20%) compared to the control group (0/20, 0%; χ2 2N=40=4.44; p<0.02). At the 6-month follow-up, effects were maintained for depressive symptom reduction (dpr6f=0.71; 95% CI: 0.19-1.61) but not treatment response. Conclusion. Disease-specific severity indicators were not related to a differential effectiveness of guided self-help for depression and diabetes. Clinical meaningful effects were observed in nonsuicidal severely depressed individuals, who do not need to be excluded from web-based guided self-help. However, participants should be closely monitored and referred to other treatment modalities in case of nonresponse.